DUAL DIAGNOSIS: HOW ADULTS DIAGNOSED WITH BIPOLAR DISORDER EXPERIENCE IN-PATIENT SUBSTANCE ABUSE TREATMENT FOR STIMULANT USE DISORDER - Van Zyl, Karina; Geyer, Stephan (Social Work/Maatskaplike Werk, 2019)
<span style="letter-spacing: -0.2pt; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Dual diagnosis has become a topic of interest in recent years. In South Africa individuals diagnosed with dual diagnosis are left without adequate services as a result of the separation of substance abuse and mental health treatment services. Through a phenomenological study the authors aimed to explore how adults diagnosed with both bipolar disorder and stimulant use disorder experienced treatment at treatment centres. Considered from a bio-psychosocial perspective, the findings give insight into service users’ living world with a dual diagnosis, their experiences, their unique needs for treatment and requirements to maintain abstinence. Recommendations for social work services at treatment centres are offered<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-bidi-font-size: 14.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">.